2004
DOI: 10.2460/javma.2004.224.388
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cisplatin combined with piroxicam for the treatment of oral malignant melanoma and oral squamous cell carcinoma in dogs

Abstract: Objective—To determine the maximum tolerated dose (MTD) of cisplatin administered with piroxicam, the antitumor activity and toxicity of cisplatin combined with piroxicam in dogs with oral malignant melanoma (OMM) and oral squamous cell carcinoma (SCC), and the effects of piroxicam on the pharmacokinetics of cisplatin in dogs with tumors. Design—Prospective nonrandomized clinical trial. Animals—25 dogs. Procedure—Dogs were treated with a combination of cisplatin (escalating dose w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
114
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 14 publications
2
114
1
3
Order By: Relevance
“…Multiple different chemotherapy protocols have been described for CMM but responses can be described as modest at best (Boria et al, 2004;Page et al, 1991;Rassnick et al, 2001). A recent study suggested adjunct post-operative carboplatin might be of use in CMM; however, as there was no control group in this study a definitive conclusion cannot be made (Dank et al, 2014).…”
contrasting
confidence: 52%
“…Multiple different chemotherapy protocols have been described for CMM but responses can be described as modest at best (Boria et al, 2004;Page et al, 1991;Rassnick et al, 2001). A recent study suggested adjunct post-operative carboplatin might be of use in CMM; however, as there was no control group in this study a definitive conclusion cannot be made (Dank et al, 2014).…”
contrasting
confidence: 52%
“…Few treatment modalities have been shown to be effective, although early radical surgery has been shown to improve the prognosis in some species. 1,7 Piroxicam was administered in the current case due to its potential antineoplastic effects. This nonsteroidal anti-inflammatory drug has been evaluated for antineoplastic effects in both dogs and humans.…”
mentioning
confidence: 99%
“…Proulx et al (5) reported that melphalan administered for COMM exerted no beneficial effects. There is limited evidence that non-steroidal anti-inflammatory drugs (NSAIDs) may exert a protective effect against malignant melanoma development in humans (22); however, in a study evaluating NSAID therapy in dogs, there was no significant difference in survival attributed to NSAID administration and NSAID therapy did not provide any survival benefit or achieved an improved therapeutic response in the treated subjects (7). Therefore, these adjuvant therapies were unlikely to confer any beneficial treatment effect in this study.…”
Section: Discussionmentioning
confidence: 62%